The Effect of Live Streaming, Cashback and Online Customer Review on Purchasing Decisions on the Shopee Application : (Case study of students of Pondok Pesantren Al-Ma'ruf Kedunglo Kediri) - Setiawan, Muhamad Aris (Universitas Nusantara PGRI Kediri, 2024)
Research aim : This research was conducted to determine and analyse the effect of live streaming, cashback and online customer reviews on purchasing decisions partially or simultaneously. Design/Methode/Approach : This research uses a quantitative research approach with causality techniques with multiple linear regression analysis data analysis techniques.. Research Finding : on the subject of santri Pesantren Al-Ma'ruf kedunglo kediri shows that online customer reviews are an important consideration in making online purchases rather than live streaming and cashback. Theoretical contribution/Originality : the results of this study indicate that live streaming and cashback have no effect on purchasing decisions in contrast to the results of research that has been conducted previously by other researchers. In addition, the results showed other factors that caused the research results to be different because the research subject used Al-Ma'ruf Kedunglo Kediri santri, whose daily lives are of course different from the general public. Practitionel/Policy implication : This research can be utilised by sellers to attract interest in buying money products on the shopee application. This is supported by a large enough opportunity that can be utilised considering that the number of santri in Indonesia reaches 3.4 million based on statistical data from the Ministry of Religion of the Republic of Indonesia dated 5 April 2022. Research limitation : This research, of course, still has many shortcomings, one of which is the cooperation between researchers and research subjects.